A visible-light driven electrochemical biofuel cell with the function of CO2 conversion to formic acid: coupled thylakoid from microalgae and biocatalyst immobilized electrodes. (8th May 2018) - Amao, Y.; Fujimura, M.; Miyazaki, M.; Tadokoro, A.; Nakamura, M.; Shuto, N.
Abstract : A new visible-light driven electrochemical biofuel cell consisting of the thylakoid membrane of microalgae immobilized on a TiO2 layer electrode as a photoanode, a formate dehydrogenase/viologen co-immobilized electrode as a cathode, and a CO2 -saturated buffer solution as the redox electrolyte, was developed. Abstract : Aerobic photosynthesis in green plants, cyanobacteria, and micro-algae has two important sites in the integral-membrane photoactive complexes, photosystems I (PSI) and II (PSII). These systems are assembled into thylakoid membranes. Thylakoid membranes with oxygen-evolution activity owing to PSII can be used in visible-light driven water photolytic materials. In this work, a new visible-light driven electrochemical biofuel-based cell consisting of the thylakoid membrane of microalgae Spirulina platensis immobilized on a nanocrystalline TiO2 layer electrode as a photoanode, a formate dehydrogenase (FDH)/viologen co-immobilized electrode as a cathode, and a CO2 -saturated buffer solution as the redox electrolyte, was developed. The actual short-circuit photocurrent of this cell was estimated to be ca. 50 μA cm −2 . Formic acid and oxygen were produced in this biofuel cell, while generating electricity from irradiated visible light. The ratio of formic acid to oxygen produced in the biofuel cell after continuous irradiation was estimated to be ∼2. Thus, formic acid and oxygen were produced stoichiometrically in this visible-light driven electrochemical biofuel cell. Thus, a new biofuel cell system with the functions of a solar cell and the ability of CO2 conversion was developed.